Determinan Minat Kunjungan Wisata Berdasarkan Aksesibilitas, Fasilitas Pendukung Pariwisata & Norma Subyektif - Rumalatu, Gilbert Alvin (Public Policy, 2020)
The purpose of this study was to examine and analyze the impact of accessibility, tourism support facilities and subjective norms on interest in tourist visits at Ora Beach and Banda Island. The population in this study were all tourists who visited 2 tourist sites in Central Maluku Regency, namely Ora Beach and Banda Island. Based on the character inherent in the population, the sampling method used is non-probability sampling through purposive sampling technique with a final sample size of 62 tourists. Testing research data begins with testing research instruments (validity and reliability tests), testing classical assumptions followed by testing multiple linear regression analysis. The results showed that accessibility, tourism supporting facilities and subjective norms were proven to have a positive and significant effect on the interest in tourist visits on Ora Beach and Banda Island. This can be proven through the regression coefficient of accessibility, tourism supporting facilities and subjective norms which, if an increase, will be followed by an increase in interest in tourist visits. Thus it can be said that the increase in the value of accessibility, tourism support facilities and subjective norms will encourage an increase in interest in tourist visits on Ora Beach and Banda Island.